Sinistral shear during Middle Jurassic emplacement of the Matancilla Plutonic Complex in northern Chile (25.4° S) as evidence of oblique plate convergence during the early Andean orogeny. (December 2022) - Mavor, S.P.; Singleton, J.S.; Heuser, G.; Gomila, R.; Seymour, N.M.; Williams, S.; Arancibia, G.
Abstract: Arc magmatism in a continental subduction zone facilitates rheological weakening of the rigid upper plate, and can accommodate the partitioned trench-parallel component of oblique subduction into an intra-arc shear zone. We document a shear zone at latitude 25.4° S near Taltal, Chile that was associated with intrusion of the Matancilla Plutonic Complex at ∼169 Ma to evaluate intra-arc deformation and possible tectonic plate configurations during this time period. Polyphase folding of Paleozoic metasedimentary rocks is overprinted by mylonitic fabrics that are most extensive in a zone up to 1.4 km wide in the thermal aureole of the granodioritic Matancilla pluton, where contact metamorphic andalusite porphyroblasts are synkinematic with fabric development. Mylonite in metasedimentary rocks is overprinted by a ∼130 Ma granodiorite (zircon U–Pb) and by ∼133 Ma postkinematic monazite (U–Pb). Within the Jurassic Matancilla granodiorite, pervasive ductile shear occurs along the intrusive contact while centimeter-scale discrete high-strain zones throughout the pluton are associated with focused hydrothermal alteration and reaction weakening. Mylonitic foliation in the metasedimentary rocks and within the pluton strikes N- to NE and dips steeply, while stretching lineations are subhorizontal on average. Kinematic indicators record dominantly sinistral shear, though some dextral or symmetric indicators and S > L fabrics suggest a component of coaxial strain and flattening. Sinistral strike-slip kinematics in the Matancilla shear zone may indicate that Middle Jurassic convergence had sinistral obliquity that was locally partitioned into the contemporaneous magmatic arc. Sinistral-oblique convergence would require the Phoenix-Farallon spreading center to be north of ∼25° S in the Middle Jurassic, providing a constraint to plate reconstructions during the early Andean orogeny. Highlights: The NNE-striking ductile Matancilla shear zone records sinistral strike-slip shear. The shear zone formed with intrusion of the Matancilla pluton at ∼169 Ma. Shear zone kinematics may reflect partitioning of oblique subduction into the arc. The Phoenix-Farallon-Gondwana triple point was likely north of ∼25°S at this time.